Knowledge Management for Professional Staffs in Hospital - Diah Mutiarasari (AIBPM Publisher, 2018)
In the era of National Health Security (NHS), every health service system is delivered under cost and quality controls so that efficient and effective health services could be achieved. Professional staffs of the hospital, including medical doctors, nurses, and midwives hold fundamental roles in hospital health services. Their fundamental roles are keys to the success of hospital perfomance. Hospital should realize the existance of professional staffs by paying attention to their knowledge, abilities, and skills. Development of knowledge, abilities, and skills is part of organization roles to manage knowledge resources in the hospital. The improvement of knowledge resources of professional staffs in the hospital provides key for the hospital to deliver the best services for the patients. Well-managed knowledge resources would improve knowledge management of hospital professional staffs and give the possibility of improving hospital perfomance. This literature study was focusing on how important knowledge management of hospital professional staffs in supporting hospital perfomance. Moreover, knowledge management would enable professional staffs learn continually by sharing experiences and improving themselves through continuing education so that improvement of service quality and profit of the hospital can be achieved. In the field of health, improvement of knowledge management for hospital staffs is expected to help understanding recent research and development, create good-quality services, decrease medical errors, and lower hospital costs, by which all of them are hoped to increase hospital competitiveness in the era of competition among hospitals. Keywords: Knowledge management, professional staff, hospital perfomance